Text Extraction from Image (International Journal of Innovative Research in Engineering & Management, 2022)
Text extraction is one of the key tasks in  document image analysis. Automatic text extraction without  characters recognition capabilities is to extract regions just  contains text. The text extraction process includes detection,  localization, segmentation and enhancement of the text  from the given input image. In this paper we present a  comparative study and performance evaluation of various  text extraction techniques.
Keywords: Text Extraction; Document Text Images; Heterogeneous Images; OCR; Text Detection